The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2903/j.efsa.2011.2259
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the substantiation of health claims related to silicon and protection against aluminium accumulation in the brain (ID 290), “cardiovascular health” (ID 289), forming a protective coat on the mucous membrane of the stomach (ID 345), n

Abstract: (ID 287, 288, 333, 334, 335, 1405(ID 287, 288, 333, 334, 335, , 1652(ID 287, 288, 333, 334, 335, , 1718(ID 287, 288, 333, 334, 335, , 1719(ID 287, 288, 333, 334, 335, , 1945, maintenance of normal bone (ID 287, 335, 1652(ID 287, 335, , 1718(ID 287, 335, , 1945, maintenance of normal joints (ID 1405(ID , 1652(ID , 1945, maintenance of normal appearance and elasticity of the skin (ID 288, 333), and contribution to normal formation of hair and nails (ID 334, 1652(ID 334, , 1719 (ID 287, 288, 333, 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…stimulating macrophages and increasing circulating lymphocytes; protection against aluminium accumulation in the brain; 'cardiovascular health'; forming a protective coat on the mucous membrane of the stomach; neutralisation of gastric acid; contribution to normal formation of collagen and connective tissue; maintenance of normal bone; maintenance of normal joints; maintenance of normal appearance and elasticity of the skin; and contribution to normal formation of hair and nails). On the basis of the data presented, the NDA Panel concluded that a cause and effect relationship had not been established between the consumption of silicon and any of the health claims proposed (EFSA NDA Panel, 2009, 2011 (JECFA, 1968(JECFA, , 2002.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…stimulating macrophages and increasing circulating lymphocytes; protection against aluminium accumulation in the brain; 'cardiovascular health'; forming a protective coat on the mucous membrane of the stomach; neutralisation of gastric acid; contribution to normal formation of collagen and connective tissue; maintenance of normal bone; maintenance of normal joints; maintenance of normal appearance and elasticity of the skin; and contribution to normal formation of hair and nails). On the basis of the data presented, the NDA Panel concluded that a cause and effect relationship had not been established between the consumption of silicon and any of the health claims proposed (EFSA NDA Panel, 2009, 2011 (JECFA, 1968(JECFA, , 2002.…”
Section: 3mentioning
confidence: 99%
“…The Panel is aware that the mineral silicon (Si) is included in the positive lists of minerals that can be added to foods, including food supplements, as defined by Annex I to Regulation (EC) No 1925No /2006 address the Terms of Reference of the current mandate and ensure consistency with previous scientific opinions issued on other sources of silicon (EFSA 2009a,b;EFSA ANS Panel, 2016), the Panel considered that bioavailability of OSA from OSA-VC should be the basis for the evaluation of the bioavailability of silicon from that source.…”
Section: Interpretation Of the Terms Of Referencementioning
confidence: 99%
See 1 more Smart Citation
“…The Panel is aware that the mineral silicon is included in the positive lists of minerals that can be added to foods, including food supplements, as defined by Annex I to Regulation (EC) No 1925No /2006 silicon is typically present in food in the form of orthosilicic acid (OSA) and as such is readily absorbed from the gastrointestinal tract in humans and then readily excreted in urine. Therefore, in order to address the Terms of Reference of the current mandate, and consistently with previous scientific opinions issued on other sources of silicon, the Panel considered bioavailability of OSA from MMST, should be the basis for the evaluation of the bioavailability of silicon from that source.…”
Section: Interpretation Of Terms Of Referencementioning
confidence: 99%
“…The Panel is aware that the mineral silicon is included in the positive lists of minerals that can be added to foods, including food supplements, as defined by Annex I to Regulation (EC) No 1925No /2006 and Annex I to Directive 2002/46/EC, respectively. Data from literature have however established that silicon is typically present in food in the form of orthosilicic acid (OSA) and as such is readily absorbed from the gastrointestinal tract in humans and then readily excreted in urine.…”
Section: Interpretation Of Terms Of Referencementioning
confidence: 99%